Penerapan Strategi Segmenting dan Targeting dalam meningkatkan Kinerja Pemasaran: Literatur review - Agus Suyatno; Syarifuddin Arief; Muhammad Asir; Muh. Abduh. Anwar; M. Dakhri Sanusi (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This paper aims to analyze the Implementation of Segmenting and Targeting Strategies in improving Marketing Performance through analysis of literature reviews in the field of marketing management. The method used in this study is a literature study by reviewing some of the results of previous studies. The writing approach in this scientific article is to use qualitative methods and library research with the help of the latest references obtained from Google Schoolers and Mendeley citation searches. The results of the research were analyzed and used as material for discussion to determine the answers to the problems of applying segmentation and targeting strategies in marketing by companies. The results of the literature review show that the existence of a Segmenting and Targeting Strategy implemented by a company can have a positive impact on marketing performance. The implementation of segmenting and targeting strategies is needed by a businessman to increase the marketing value of the products being sold. This is because segmenting and targeting strategies have a positive influence on marketing performance. The better the segmenting and targeting strategies are carried out, the higher the sales that will be generated. Keywords: Marketing Performance, Literature Review, Segmenting, Targeting.